The Role of Assessment in Teaching English for Specific Purposes - Jinani Firdausiyyah Shohib; Putri Anggun Nur Imamah Ulfa Aldama; Silvia Harira Gudsy; Moh. Ali Masduki; Muhammad Alfa Hosen (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study aims to explore the practices and perceptions of tutors in implementing assessment in English for Specific Purposes (ESP) instruction at non-formal language course institutions. A quantitative method was used, involving data collection through questionnaires with both closed and open-ended questions, complemented by an online interview to deepen the understanding of assessment implementation. The results show that diagnostic and formative assessments are the most frequently used types (100%), while performance-based and project-based assessments are used by 50% of the respondents. None of the tutors reported using self-assessment, indicating a limited variety in assessment methods applied. The main purposes of assessment include identifying students’ learning needs, monitoring progress, and evaluating teaching effectiveness. Despite facing challenges such as limited time and low student motivation, tutors managed to apply solutions like group discussions and peer feedback. Assessment was found to positively impact both students’ skill development and tutors’ understanding of -learners’ needs. The study concludes that assessment in ESP plays a strategic role not only as an evaluation tool but also as a diagnostic and formative mechanism that supports continuous learning. Therefore, proper understanding and contextual adaptation are essential in maximizing the role of assessment in ESP instruction.